Two Weights and Two Measures: the projection of coloniality in migration and citizenship Policies of the European Union - Silva, Karine de Souza (2019)
The present article aims to show that the European Union's migration and citizenship policies reproduce coloniality on a supranational scale because they perpetuate the colonial hierarchies between Europeans and non-Europeans based on the idea of ”‹”‹race. The hypothesis arises that the process of supranationalisation of migration and of common identity in the EU reiterates the elements of coloniality due to the strongly racial conception they contemplate, separating the ex-colonizers from the ex-colonized by abyssal lines. The argument that European regional integration exceeds the elements of social classification present in the European national state, especially with regard to non-European migrations, is deconstructed. Thus, the first part of the present paper confronts, from the literature, the proposal of integration of the European Union with the colonial structures of power, of knowledge and of being about race and ethnicity. Next, the second section presents the migration and citizenship policies of the European Union. Finally, the last part demonstrates, from the summary of rights and restrictions exposed, how the coloniality of being is reproduced on a supranational scale, from the analysis of each social classification between Europeans and non-Europeans.